1993
DOI: 10.1111/j.1744-7348.1993.tb04106.x
|View full text |Cite
|
Sign up to set email alerts
|

Postharvest disease control in mangoes using high humidity hot air and fungicide treatments

Abstract: The disease control efficacy of quarantine heat treatments developed for fruit fly disinfestation in mangoes cv. Kensington Pride was evaluated in this study. Heat was applied using high humidity (>95% r.h.) hot air (HHHA) at temperatures ranging from 4749°C.Anthracnose, caused by Colletotrichum gloeosporioides, was well controlled in mangoes heated to a core temperature of 46"C, 47°C or 48°C for 24, 10 or 8 min respectively, prior to ripening at 23°C for 16 days. Stem end rot, caused by Dothiorella dominicana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 9 publications
1
14
0
Order By: Relevance
“…Disease incidence was found lesser at removal stage which could be possibly due to the application of fungicide and hot water treatment. Fungicidal application along with hot water treatment is reported to suppress the disease incidence during mango storage, to acceptable levels as reported by many researchers (Coates et al, 2008;Dang et al, 2008). These results are in accordance with the findings of Yahia (1998) who reported that hot water treatment along with Sportak or Thiabendazole application reduced the disease incidence during storage of mango.…”
Section: Discussionsupporting
confidence: 90%
“…Disease incidence was found lesser at removal stage which could be possibly due to the application of fungicide and hot water treatment. Fungicidal application along with hot water treatment is reported to suppress the disease incidence during mango storage, to acceptable levels as reported by many researchers (Coates et al, 2008;Dang et al, 2008). These results are in accordance with the findings of Yahia (1998) who reported that hot water treatment along with Sportak or Thiabendazole application reduced the disease incidence during storage of mango.…”
Section: Discussionsupporting
confidence: 90%
“…Dipping oranges for 42 min in water heated to 458C significantly reduced decay caused by Colletotrichum gloeosporioides, Penicillium digitatum and P. italicum (Williams et al, 1994). Vapour heat at temperatures ranging from 47 to 498C controlled C. gloeosporioides in mangoes (Coates et al, 1993), whilst exposing tomato fruits to 388C for 3 days prior to storage inhibited decay due to B. cinerea. (Fallik et al, 1993).…”
Section: Introductionmentioning
confidence: 95%
“…Many studies demonstrate that the efficacy of Imazalil and/or Prochloraz increases when applied in hot water in a number of fruits such as mango (Spalding & Reeder, 1986;Johnson et al, 1990;Prusky et al, 1990;Dodd et al, 1991;Coates et al, 1993;McGuire & Campbell, 1993;Waskar, 2005); melons (Carter, 1981b;Mayberry & Kartz, 1992), taro corms (Quevedo et al, 1991), red tamarillos (Yearsley et a., 1988), and in citrus fruit (Ansari & Feridoon, 2008).…”
Section: Thiabendazole and Imazalilmentioning
confidence: 99%